Factors influencing sex education for in-school adolescents in Ibadan, Nigeria (2010)
It is common among Nigerian parents to prevent their adolescents from receiving information about sexuality, believing, erroneously, that ignorance would enable them maintain chastity: Often, this overlooked aspect of essential family responsibility is taken over by peers who usually give false, incomplete and misleading sexual orientation. Consequently, adolescents with poor assertive skills engage in premarital sex and face the concomitant effects, such as unplanned pregnancy, abortion, sexually transmitted infections including HIV, dropping out of school, among others. This study therefore examined the factors influencing life-saving education among in-school adolescents in Ibadan, in order to understand the context of silence that pervades the sexuality information corridor. Quantitative data were collected through a multistage sampling technique, beginning with the random selection of six schools. Each of the schools was stratified into junior and senior classes, and from these strata, 800 respondents were chosen using the simple random method. In addition, 15 in-depth interviews (IDIs) were conducted among a cross-section of Ibadan residents. Results indicated that the majority of respondents whose mothers were engaged in private businesses have a more negative attitude towards sexuality education than those whose mothers are either civil servants, professionals or lecturers/teachers. The parents' level of education showed a consistent association with perception about sexuality education; those with the lowest level of education had the lowest percentage (28.6%) of positive perception towards such education, while those with the highest education represent those with the highest percentage (60%) of positive perception. Factors that affect sex education are multiple and require intervention at different levels to make it an integral part of socialization, both at home and in school.